SEPARATION OF SURKHANDARYA REGION INTO LANDSCAPE TYPES AND ITS SIGNIFICANCE IN AGRICULTURE (Scientific journal of the Fergana State University, 2024)
Agricultural geography, which is one of the most interesting topics of today, is the territorial organization of agriculture and the laws of its development, and its main task is to supply the population with food, clothing products, and a number of industries, in particular: (food, fodder, textiles , pharmaceuticals and other) consists of supplying raw materials. A number of achievements have been made in the development of agriculture in Surkhandarya region. Today, the main agricultural sectors of the region are cotton growing, grain growing, horticulture, cocoon growing, lemon growing. Dry farming (mainly wheat and barley) is practiced in the foothills of the mountains. However, taking into account the landscape factor in the use of agricultural land is a requirement of today. Unfortunately, today has its own requirements and rules. In particular, since the landscapes of the area used for agricultural purposes are being studied from the point of view of long-term sustainable use in agriculture, the landscape factor is considered relevant in this research. Therefore, using the "geological and natural map of surkhandarya region" published in 2012 by the state committee "yergeodezkadastr" prepared with the support of Surkhondarya region administration and land resources and state cadastre department of Surkhondarya region, two large altitude regions were separated, and in turn, these two plains and mountains divided into landscape pointers. These elevation regions are used to compare and predict future agricultural landscapes using GIS software and develop suggestions and recommendations.